Efficient Biomedical Waste Management- Need of the Time: A Lesson Learnt From COVID-19 Pandemic - Kiran Prakash Kanaparty; Deepti Vemu; Syeda Fahada Zia; Mavatkar Munnaji Vyankatesh; Gavireddy Sravani (Journal of Epidemiology and Public Health, 2024)
Background: Medical waste management (MWM) is of concern to the medical and general com-munity. Adequate knowledge regarding the management of healthcare waste is an important precursor to the synthesis of appropriate attitudes and practices of proper handling and disposal of medical waste by healthcare workers (HCWs). This study aimed to investigate the knowledge, attitudes, and practices of doctors, nurses, laboratory technicians, and housekeeping staff, regarding BMW management at a tertiary hospital in Telangana.Subjects and Method: This was a cross‑sectional study carried out at a tertiary health care center in Mahbubnagar district, Telangana, India. A stratified sampling technique was used to select the different cadre of healthcare providers from the hospital. A self‑administered questionnaire assessing the knowledge, attitude, and practices of 300 study participants was prepared. Data were analyzed using SPSS software version 26. Descriptive statistics were used to summarize the data.Results: The majority of respondents were nursing staff 43% (143/300) followed by doctors, interns, sanitation workers, and lab technicians. About 3/4th of the HCWs had experience of more than 3 years. Only 65% of the doctors have correct knowledge of the colour coding of bags. About only 20% of the nursing staff practiced segregation of the waste on-site. The practice of hand washing was significantly higher among female HCWs (p = 0.010).Conclusion: This study showed that there is a clear lack of BMW management among the HCW especially class IV staff who handle a large. Thus ongoing training should be provided to HCWs on MWM, with more attention to knowledge of regulatory requirements, and involvement of HCWs in the development of MWM policies to enhance compliance.